Sistem Monitoring Tingkat Kebisingan Menggunakan LED RGB Indikator Berbasis Arduino Uno - andri nurdiyansah; Muhamad Hilmansyah Susanta (LPPM Politeknik Pajajaran ICB Bandung, 2026)
The advancement of microcontroller technology has enabLED the development of simple and efficient environmental monitoring systems. One common issue in urban areas is noise pollution, which can negatively affect human comfort and health. This study aims to design and implement a noise level monitoring system based on Arduino Uno using a KY-038 sound sensor and RGB LED indicators. The system operates by reading analog values from the sensor within a range of 0–1023, which are then classified into three categories: low, medium, and high based on pRedefined threshold values. The classification results are displayed through RGB LEDs using Green, yellow, and Red colors as visual indicators of environmental conditions. The research method includes Hardware design, Software development using Arduino IDE, and system testing under various noise conditions. The testing results show that the system is capable of detecting sound intensity changes in real-time with fast response and good accuracy. Furthermore, the system demonstrates consistent performance in classifying noise levels according to the defined thresholds. Therefore, this system can serve as a practical, low-cost, and easy-to-implement alternative for noise monitoring